A rare case of persistent pupillary membrane associated with high myopia and amblyopia - Gupta, Y; Gupta, M; Sambhav, K; Mittal, T (Nepalese Journal of Ophthalmology, 2010)
Purpose: To present the management of a rare case of persistent pupillary membrane (PPM) associated with high myopia and amblyopia. Case: A 12-year-old boy presented with progressive diminution of vision in the right eye since childhood. Examination (OD) showed several fine strands of iris attached to the collarette and to the anterior lens capsule with a clump of iris pigment adherent over it. Some of these strands even wrinkled on pupillary contraction. The patient was also examined on slit-lamp.The patient was operated for lens extraction with PCIOL implantation. Results: The patient regained useful vision after surgery. Conclusion: This is a rare case of persistent pupillary membrane associated with high axial myopia. Keywords: persistent pupillary membrane; myopia; amblyopia DOI: 10.3126/nepjoph.v2i1.3708 Nep J Oph 2010;2(1) 68-70